Pengaruh Website Information Dan Brand Awareness Melalui Minat Orang Tua Dalam Memilih Sekolah DI SDSC - Bare, Maria Magdalena; Susanto, Hendro (Research and Community Service UNIVERSITAS KALBIS, 2025)
The aim of this research is to analyze the influence of school websites and brand awareness in influencing parents' decisions in choosing an elementary school at SDSC. The research population was respondents who were parents of students at SDSC, collecting 534 respondents. The data collection method is quantitative with descriptive analysis techniques and inferential analysis. The research results show that information on the website and brand awareness have a positive and significant effect on interest, meaning that the information presented on the SDSC school website has a large and significant impact in attracting interest in choosing an elementary school.